2020
DOI: 10.1111/adj.12792
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Individual‐level and Area‐level social disadvantage and oral health behaviours in Australian adolescents

Abstract: Background: Oral health behaviours are significant determinants of oral health. There is evidence that socioeconomic position influences oral health behaviours, but little is known about this association during adolescence. This study aims to investigate the association between social disadvantage (individual and area level) and oral health behaviours among Australian adolescents. Methods: This study utilized data from the Longitudinal Study of Australian Children (LSAC). The sample consisted of 2877 adolescen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
(50 reference statements)
1
1
0
Order By: Relevance
“…In the 18-24-year group, individuals from neighborhoods with a higher household income were significantly more likely to receive preventive services and significantly less likely to receive treatment services. This is in keeping with individuallevel research among both adolescents [36] and adults [37]. The geovisualization of these variables also showed that the changes in dental care outcomes were more pronounced in some FSA codes when compared to others The results of this study show neighborhoodlevel discrepancies in dental care outcomes in both the age groups studied.…”
Section: Discussionsupporting
confidence: 88%
“…In the 18-24-year group, individuals from neighborhoods with a higher household income were significantly more likely to receive preventive services and significantly less likely to receive treatment services. This is in keeping with individuallevel research among both adolescents [36] and adults [37]. The geovisualization of these variables also showed that the changes in dental care outcomes were more pronounced in some FSA codes when compared to others The results of this study show neighborhoodlevel discrepancies in dental care outcomes in both the age groups studied.…”
Section: Discussionsupporting
confidence: 88%
“…2 Total streptococci = SSA, total bacterial count = CDC, total Mutans streptococci = MSKB. 3 Body mass index = BMI. 4 p-values were calculated via chi-square and Fisher's exact tests.…”
Section: Tooth Brushing Frequencymentioning
confidence: 99%
“…Despite the use of fluoride and sealants [1], 57% of adolescents in the United States have caries in their permanent teeth [2]. Adolescents' high risk for caries is associated with poor hygiene and high consumption of soda [3]. In lieu of the recommended two minutes of brushing, adolescents often apply excessive pressure for less time, leading to problems that range from gingivitis to chronic diseases [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…27 In 11 out of the 15 papers, references to 'vulnerable populations' as high risk groups were made due to numerous diverse characteristics linked to poor diets and health outcomes. These 'at risk' groups were farmworkers, 28 single parent households, 29 those who are unemployed, 29,30 obese and overweight, 31 migrants 32 or ethnically diverse groups, 33,34 frequent consumers of SSBs, 26,31 children or adolescents, 35,36 people with disabilities, older people, those living in poverty, and people affected by alcoholism and drug addiction. 29,33 Five studies provided vague or unclear definitions over who might be included in the term 'vulnerable populations', or the reasons why, and did not explain this concept further.…”
Section: Vulnerable Populationsmentioning
confidence: 99%